Optimization of the epoxidation process parameters of fatty acid methyl esters using Response Surface Methodology (RSM) based on Central Composite Design (CCD) - Derahman, Aishah; Zainal Abidin, Zurina (UiTM Press, 2022)
The objective of this study was to optimize the epoxidation of fatty acid methyl esters (FAME) derived from Jatropha oil. This experiment was carried out with peracetic acid generated in situ by using hydrogen peroxide and acetic acid. A response surface methodology (RSM) central composite design (CCD) was used, with one response variable, the percentage (%) of epoxidation yield. The factors evaluated were temperature (50-80°C), the molar ratio of hydrogen peroxide (HP) to unsaturation (1.1-2 mol), the molar ratio of acetic acid (AA) to unsaturation (0.5-0.8 mol), and time (2-7 hours). The optimum percentage of epoxidation yield (90.98%) was at the condition of 65°C reaction temperature, HP to unsaturation molar ratio of 2.19, AA to unsaturation molar ratio of 0.65 for 6 hours. The formation of epoxides product (oxirane) was confirmed using Fourier transform infrared spectroscopy oxirane peaks (doublet) at 825 and 843 cm-1. The result showed good agreement with the predicted values from the RSM model.